Problem dan Pengembangan Pendidikan Islam di Indonesia - Anisyah Rahmadania; Qolbi Khoiri (Journal on Education, 2023)
Quality, relevance, elitism, and management are the four main crises that are at the heart of the problem of education in Indonesia. On these four issues, various quantitative indicators have been proposed, including a comparison of the educational situation in Asian countries. In the laws and regulations governing the state education system, Islamic education is a component of national education. This discussion discusses the problems and development of Islamic education as a formulation of the existing problems. A component of the overall state policy is education policy. so that national education in the end must return to its goal, namely to empower the community by returning the community's autonomy to develop themselves. The following are the basic principles of the Islamic education system: 1) Based on the Islamic creed, Islam establishes curriculum principles, methods and educational goals. 2) Faith development should be the focus of education. 3) The aim of education is to bring out the best in everyone and minimize the worst in them while maintaining harmony with human nature. Islamic education is urged to develop new operational strategies and tactics in addition to curriculum and management tools. In pedagogical, sociological, and cultural terms, these strategies and tactics demonstrate their role to the point that they require an overhaul of models and institutions to make them more effective.